Islamic content on screens: analysing Gen Z’s perceptions on digital media’s influence on language and religiosity - Mohamed Salleh, Rabiah Tul Adawiyah; Muhsin, Sayyed Mohamed (Kimlik Yayınevi Köşk Mah. Ahmet El Biruni Cad. No: 8 Melikgazi / KAYSERİ, Turkey, 2025)
The digital age fundamentally alters religious engagement, particularly for young Muslims engaging with a constant stream of online content. Islamic content, including reminders disseminated widely across social media, represents a significant aspect of this digital religious landscape for Generation Z. While discussions often highlight the negative effects of digital media, less research explores how Gen Z perceives the influence of this digital exposure on their own lives. Focusing on students at the International Islamic University Malaysia (IIUM), this study investigates Gen Z’s perceptions regarding Islamic content encountered on social media. It specifically examines the perceived influence of engaging with this content on their linguistic practices (language use, vocabulary related to Islam) and their overall religiosity (encompassing identity, belief, and practice). Utilising a survey-based methodology, this research quantifies key variables, including self-reported exposure, engagement patterns, perceptions of influence, and religiosity levels, and analyzes the relationships between them. Findings reveal the nuanced interplay between digital religious engagement and identity expression as understood by young Muslims themselves. This work provides valuable insights for educators, content creators, and digital da’wah initiatives within the IIUM context and potentially beyond